Low-Zone IL-2 Signaling: Fusion Proteins Containing Linked CD25 and IL-2 Domains Sustain Tolerogenic Vaccination in vivo and Promote Dominance of FOXP3+ Tregs in vitro - DeOca, Kayla B.; Moorman, Cody D.; Garcia, Brandon L.; Mannie, Mark D. (Frontiers in Immunology, 2020)
Low-zone IL-2 signaling is key to understanding how CD4+ CD25high FOXP3+ regulatory T cells (Tregs) exhibit dominance and overgrow conventional effector T cells (Tcons) that typically express lower levels of the IL-2 receptor alpha chain (i.e., CD25). Thus, modalities such as low-dose IL-2 or IL-2/anti-IL-2 antibody complexes have been advanced in the clinic to selectively expand Treg populations as a treatment for chronic inflammatory autoimmune diseases. However, more effective reagents that efficiently lock IL-2 signaling into a low signaling mode are needed to validate and exploit the low-zone IL-2 signaling niche of Tregs. This study focuses on CD25-IL2 and IL2-CD25 fusion proteins (FPs) that were approximately 32 and 320-fold less potent than IL-2. These FPs exhibited transient binding to transmembrane CD25 on human embryonic kidney (HEK) cells, had partially occluded IL-2 binding sites, and formed higher order multimeric conformers that limited the availability of bioactive IL-2. These FPs exhibited broad bell-shaped concentration ranges that favored dominant Treg outgrowth during continuous culture and were used to derive essentially pure long-term Treg monocultures (∼98% Treg purity). FP-induced Tregs had canonical Treg suppressive activity in that these Tregs suppressed antigen-specific proliferative responses of naïve CD4+ T cells. The in vivo administration of CD25-IL2/Alum elicited robust increases in circulating Tregs and selectively augmented CD25 expression on Tregs but not on Tcons. A single injection of a Myelin Oligodendrocyte Glycoprotein (MOG35-55)-specific tolerogenic vaccine elicited high levels of circulating MOG-specific Tregs in vivo that waned after 2–3 weeks, whereas boosting with CD25-IL2/Alum maintained MOG-specific CD25high Tregs throughout the 30-day observation period. However, these FPs did not antagonize free monomeric IL-2 and lacked therapeutic efficacy in experimental autoimmune encephalomyelitis (EAE). In conclusion, these data reveal that CD25-IL2 FPs can be used to select essentially pure long-term lines of FOXP3+ CD25high Tregs. This study also shows that CD25-IL2 FPs can be administered in vivo in synergy with tolerogenic vaccination to maintain high circulating levels of antigen-specific Tregs. Because tolerogenic vaccination and Treg-based adoptive immunotherapy are limited by gradual waning of Tregs, these FPs have potential utility in sustaining tolerogenic Treg responses in vivo.